Health literacy and e-health literacy among Arabic-speaking migrants in Sweden: a cross-sectional study - Lina Bergman; Ulrica Nilsson; Karuna Dahlberg; Maria Jaensson; Josefin Wångdahl (BMC, 2021)
Abstract Background Health inequities arise when the public cannot access and understand health information in an easy, accessible, and understandable way. Evidence supports that health literacy (HL) is a determinant for health outcomes, and when HL is limited this may have a major impact on morbidity as well as mortality. Migrants are known to have limited HL. Therefore, this study aimed to explore comprehensive health literacy (CHL) and electronic health literacy (eHL) among Arabic-speaking migrants in Sweden. Methods This was a cross-sectional observational study conducted in Sweden. A total of 703 persons were invited to participate between February and September 2019. Two questionnaires - the Health Literacy Survey European Questionnaire (HLS-EU-Q16) and the eHealth Literacy Scale (eHEALS) - and questions about self-perceived health and Internet use were distributed in Swedish and Arabic. Various statistical analyses were performed to determine the associations for limited CHL and eHL. Results A total of 681 respondents were included in the analysis. Of these, 334 (49%) were native Arabic-speaking migrants and 347 (51%) were native Swedish-speaking residents. CHL and eHL differed between the groups. The Arabic speakers had significantly lower mean sum scores in eHL 28.1 (SD 6.1) vs 29.3 (6.2), p = 0.012 and lower proportion of sufficient CHL 125 (38.9%) vs 239 (71.3%), p < 0.001 compared to Swedish speakers. Multiple regression analysis showed on associations between limited CHL and eHL and being Arabic speaking, less Internet use, and not finding the Internet to be important or useful. Furthermore, longer time spent in Sweden was associated with higher levels of CHL among the Arabic speakers, (OR 0.94, 95% CI 0.91-0.98, p < 0.01). Conclusions CHL and eHL differ between Arabic-speaking migrants and native Swedish speakers, but also between Arabic speakers who have lived different lengths of time in Sweden. Though it seems that the eHealth literacy is less affected by language spoken, the Internet is suggested to be an appropriate channel for disseminating health information to Arabic-speaking migrants.